L'eutrophisation - Pinay, Gilles (éditions Quae, 2018)
Eutrophication affects many lakes, reservoirs, rivers and coastal areas in France and throughout the world. It has a major disruptive effect on aquatic ecosystems and an impact on assets and associated services, human health and economic activities. This book sets out the available scientific knowledge on this phenomenon. It identifies existing levers for action and the national and international provisions introduced to monitor and combat eutrophication.